Capillary-venous malformation monitored for 20 years. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
A vascular malformation can simulate an infantile hemangioma, but differs because it lacks the rapid growth phase in the first months of life and especially lacks the phase of involution. Our patient has a mixed capillary and venous malformation, the latter being become evident after the first decade of life. She never presented complications of thrombotic type and coagulation tests resulted within the normal limits, but the esthetic damage was significant because the lesion stood on an exposed area. The treatment of vascular malformations is difficult and it is based on transcutaneous sclerotherapy, laser therapy and surgery. The therapy is nevertheless charged with heavy side effects, local and sometimes systemic; therefore it should be carried out with caution in specialized centers.